A Systematic Literature Review of EFL/ESL Teachers' Emotional Experiences - Fatma Toköz; A. Beyza Şahin Yıldırım (Educational Academic Research)
There is a growing body of literature regarding language teachers’ emotions and their impact on teaching practices. However, the connection between their emotional experiences and their impact on teaching remains substantial. Evidently, integrative research methods are necessary to provide a more dynamic perspective on this complex subject. Thus, this study is based on the concept that emotions are complex and dynamic aspects of language teachers and learners during the learning and teaching stages. It is also motivated by the interest in conducting systematic literature reviews, the dynamic shift in language teaching, and the focus on a complex research phenomenon. On this basis, this study builds on 14 research articles conducted over the last ten years concerning teacher emotions. The study also used the Preferred Reporting Items for Systematic Reviews and Meta-Analysis checklist. The findings suggest that further research is needed to explore the variation among language teachers’ emotions in different contexts and their impact on teaching practice. This study also provides insights into professional identity, professional development, and fostering emotional connections between teachers and students.